Surveillance of surgical site infections to determine incidence, risk factors and microbiologic spectrum following obstetric and gynaecological surgeries - Panicker, Seetha; Chitra, T. V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Surgical site infections (SSI) are one of the major health problems throughout the world with an incidence of 3%-16%. Hospital acquired surgical site infection is further complicated by the emergence of multi drug resistant strains. SSI surveillance is an established monitoring tool and has been shown to reduce infection rates. The importance of preventing surgical site infections is well recognized since they lead to increased morbidity, prolonged hospital stay, need for readmission, high end antibiotic treatment and re-surgery. This study was undertaken to determine the incidence, risk factors, and microbiological spectrum of surgical site infections and to identify the multidrug resistant strains. Analysis of the effectiveness of the existing surveillance methods was also done. Methods: This retrospective study was done for a period of 1-year form Jan 2016 to Dec 2016. All patients with infection following caesarean section and abdominal and vaginal hysterectomy were included. Laparoscopic surgery and patients with preexisting infection were excluded. Results: Incidence of SSI in present study is 5.27%. The major risk factors identified were obesity, diabetes and prolonged operating time. The commonest infective organism was Klebsiella Pneumoniae in 37% of which 19% were ESBL producing and 3.8% were carbapenemase producing. E. coli was identified in 20% of isolates. The incidence of ESBL in both isolates was higher. Conclusions: Regular audit of SSIs is a very effective tool to analyse risk factors, identify causes and plan strategies to prevent infection.